An Agenda for Future Research on Applicant Reactions to Selection Procedures: A Construct-Oriented Approach - CHAN, David (Institutional Knowledge at Singapore Management University, 2004)
This article offers an agenda for future research on applicant reactions to selection procedures. Advocating a construct-oriented approach, we propose that future research focuses attention on fundamental issues subsumed under seven distinct although related areas namely: (1) dimensions of applicant reactions, (2) changes in applicant reactions over time, (3) determinants of applicant reactions, (4) applicant reactions and test constructs, (5) criterion outcomes of applicant reactions, (6) reactions to new technology in testing, and (7) methodological and data analysis issues. [PUBLICATION ABSTRACT]